THE IMPLEMENTATION OF LEGAL PROTECTION AND CERTAINTY PRINCIPLES FOR CONSUMER OF FOOD AND BEVERAGE RELATED TO MICRO AND SMALL BUSINESSES IN ACEH - Sri Walny Rahayu, Teuku Ahmad Yani (Hamdard Islamicus, 2020)
The Special Province of Aceh government has legal pluralism in its administrations. In its governance system, Islamic law and customary law are also applied besides the state law. Ulama (Islam Scholars) also have important roles in determining regional policies. Actually, against Islamic law, the process of food and beverage trade by micro and small business actors still uses hazardous and prohibited materials such as formaldehyde, borax and RhodamineB. This study aims to analyze and to explain the application of protection and legal certainty of food consumers and beverages marketed by Micro, Small and Medium Enterprises (MSMEs) associated with the halal product guarantee concept. It also explains the concrete policies adopted by the Government of Aceh as a competitive consumer protection standard. This type of research is sociological juridical, which observes reactions and interactions when the norm system relating to consumer protection and the guarantee of halal products works in the community. The approach was used sociologically and qualitatively. Primary research data wasgathered from social facts processed by using descriptive analysis methods and was presented in a qualitative form. The research results show factors of the lack of consumer’s protection, namely: business actors’ difficultiesin obtaining capital, knowledge, and skills, lack of product innovation, difficulties in distributing goods, no product-branding, no consumer-loyalty program, lack of understanding of the rules of consumer protection and halal product guarantees, the traditionalaccounting records, not having business license, lack of local government supervision and the disharmonized between laws and regulations. Concrete policies stipulated by the Government of Aceh arethe ease of business licensing procedures and acceleration of ownership of non-paid halal certificates, especially for processed food business actors produced by home industry. Thus it is recommended to establish a Dispute Settlement Agency (BPSK), Non-Governmental Protection Institutions (LPKSM) in each regency/city; to conduct socialization, education as well as promotion of halal product guarantees in various events; to collaborate with the private sector as an assisting partner that can be used as a mentor for micro and small business actor in anticipating the industrial revolution 4.0